Apple Apple Inc. and Global Supply Chain Transformation: A Study of Production Network Expansion to Southeast Asia: Inc. and Global Supply Chain Transformation: A Study of Production Network Expansion to Southeast Asia - TIA LISTIA; Ines Widy; Fifi Agus (POLTRANS: Journal of Politics and Social Transformation, 2026)
This study examines the transformation of Apple Inc.’s global supply chain within the evolving landscape of the contemporary international political economy, with particular attention to the diversification of its production network toward Southeast Asia and India. The study is motivated by the increasing complexity of global production systems resulting from intensifying geopolitical tensions between the United States and China, trade and technology competition, supply chain disruptions during the COVID-19 pandemic, and growing pressures on multinational corporations to strengthen production resilience, flexibility, and risk management. Against this background, the study aims to analyze the nature of Apple’s global supply chain transformation and identify the key economic, geopolitical, and strategic factors driving the geographical diversification of its production activities. Employing a qualitative descriptive-analytical approach, the research draws upon a literature review and analysis of secondary sources concerning global value chains (GVCs), supply chain resilience, de-risking strategies, geopolitical risk, and the international production structure of Apple Inc. The findings indicate that Apple has gradually reduced its excessive dependence on China by adopting a China Plus One strategy, particularly through the expansion of manufacturing activities and supplier networks in Vietnam and India. Nevertheless, China continues to function as a critical and deeply embedded hub within Apple’s global production ecosystem due to its extensive manufacturing capabilities, mature supplier networks, skilled labor base, and integrated industrial infrastructure. Rather than representing a complete relocation or decoupling from China, Apple’s supply chain transformation reflects a gradual process of geographical diversification that has produced a more distributed, flexible, and adaptive multipolar production structure. The study argues that this transformation cannot be understood solely through the conventional logic of cost efficiency and comparative advantage, but must also be examined through the interconnected dynamics of geopolitics, economic security, technological competition, supply chain resilience, and corporate risk mitigation. By highlighting the interaction between corporate strategy and shifts in the international political economy, this study contributes to the literature on global value chains and de-risking by demonstrating how multinational corporations strategically reorganize global production networks in response to geopolitical uncertainty while simultaneously maintaining established production hubs that remain essential to global manufacturing efficiency.